Independent quantum systems and the associativity of the product of quantum observables - Fredenhagen, Klaus (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2019)
We start from the assumption that the real valued observables of a quantum system form a Jordan algebra which is equipped with a compatible Lie product characterizing infinitesimal symmetries, and ask whether two such systems can be considered as independent subsystems of a larger system. We show that this is possible if and only if the associator of the Jordan product is a fixed multiple of the associator of the Lie product. In this case it is known that the two products can be combined to an associative product in the Jordan algebra or its complexification, depending on the sign of the multiple.